2012
DOI: 10.1002/mds.25197
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Parkinson's disease: A review of case‐control polysomnography studies

Abstract: The link between Parkinson's disease (PD) and certain primary sleep disorders has yet to be clarified. We performed a systematic review of case-control polysomnography studies to evaluate the relationship between PD and sleep disorders. A PubMed literature search and bibliography review yielded 15 case-control polysomnography studies in patients with PD. Studies differed by recruitment methods, duration of polysomnography monitoring, and sleep parameters measured. Subjective sleepiness was greater in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
70
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 27 publications
9
70
0
2
Order By: Relevance
“…On the contrary three of five studies suggested that the control group had increased OSAS compared with the PD group. 26 We also found five previous studies analyzing RBD in patients with PD. The RBD diagnostic criteria were modified in 2005, requiring RWA to be demonstrated by EMG in submental and limb muscles and the existence of a clear history of dream-enacting behaviors, suggesting that PSG is essential for establishing an accurate diagnosis of RBD.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…On the contrary three of five studies suggested that the control group had increased OSAS compared with the PD group. 26 We also found five previous studies analyzing RBD in patients with PD. The RBD diagnostic criteria were modified in 2005, requiring RWA to be demonstrated by EMG in submental and limb muscles and the existence of a clear history of dream-enacting behaviors, suggesting that PSG is essential for establishing an accurate diagnosis of RBD.…”
Section: Discussionsupporting
confidence: 61%
“…Overnight polysomnography is an objective method of measuring the parameters of sleep architecture and pathophysiological events during sleep. 25 To our knowledge, although several studies have been conducted with PD patients using PSG, 26 sleep disorders in ET patients have not previously been investigated using this technology. In our study, we found no differences among PD, ET, and control groups in terms of TST, WBS, SEI, SCI, CA, AHI, RDI, arousal indices, or PLMI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in PD patients, lower levels of decline in the minimal or mean nocturnal oxygen saturation levels than in AHImatched controls were observed [17,21]. In contrast, recent studies suggest that the comorbidity of SAS is not more frequent in PD patients than in the general population, and thus, it may not a relevant issue in PD [10,11,134]. Moreover, it has been argued that SAS may not play a major role in EDS in PD.…”
Section: Sleep Apnea Syndromementioning
confidence: 75%